2019
DOI: 10.3389/fonc.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducer and Activator of Transcription (STATs) Proteins in Cancer and Inflammation: Functions and Therapeutic Implication

Abstract: Signal Transducer and Activator of Transcription (STAT) pathway is connected upstream with Janus kinases (JAK) family protein and capable of integrating inputs from different signaling pathways. Each family member plays unique functions in signal transduction and crucial in mediating cellular responses to different kind of cytokines. STAT family members notably STAT3 and STAT5 have been involved in cancer progression whereas STAT1 plays opposite role by suppressing tumor growth. Persistent STAT3/5 activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
202
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(206 citation statements)
references
References 192 publications
(233 reference statements)
3
202
0
1
Order By: Relevance
“…Cell transduction and transcription activator 3 (STAT3) is an important member of the signal transduction and transcription activator family. Continuous activation of STAT3 can lead to abnormal cell proliferation and malignant transformation [16,17]. STAT3 gene is located on 17q21.2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Cell transduction and transcription activator 3 (STAT3) is an important member of the signal transduction and transcription activator family. Continuous activation of STAT3 can lead to abnormal cell proliferation and malignant transformation [16,17]. STAT3 gene is located on 17q21.2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…the STAT3 inhibitors AZD9150 in non-Hodgkin's lymphoma, OPB-51602 in nonsmall-cell lung cancer and napabucasin in advanced colorectal cancer, and the STAT5 inhibitor pioglitazone (added to imatinib) in chronic myeloid leukaemia. [10][11][12][13][14][15] The role of STATs in the human epithelial carcinogenesis has been poorly investigated, but in the era of studies on inhibitors targeting STAT proteins, this topic seems to be worth exploring. Chan et al reported that Stat3 in mice is required for de novo epithelial carcinogenesis, showing that Stat3 is involved in both initiation and promotion of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although an overall mechanism of action was not identified, these studies suggest that STATs may contribute to tumor growth and progression of obesity-related cancers. Based on the roles of STATs in a wide variety of cancer types [93], future studies will likely reveal critical roles of STAT proteins in obesity-related cancers.…”
Section: Stats and Obesity-related Cancersmentioning
confidence: 99%